Role of essential oils as feed additives in egg production and future perspectives. - Muhammad Naim, Rosli; Lani, Mohd Nizam; Tang, Shirley Gee Hoon; Abdul Mutalib, Maisarah; Ariffin, Indang Ariati; Tang, Hooi Chia; Yong, Su Ting; Loh, Teck Chwen (Biome Scientia Sdn Bhd, 2024)
The use of essential oils (EOs) in poultry production has gained attention due to their potential benefits as natural alternatives to feed additives. However, there is a lack of comprehensive reviews synthesizing the existing literature on the application of EOs in laying hen production. This review paper aims to discuss this research gap by providing a critical review of the current state of knowledge regarding the efficacy, modes of action, and practical considerations of using EOs in layer diets. Through a narrative review of empirical studies, the paper evaluates the effects of various EOs on key performance parameters in laying hens, including egg production, egg quality, feed efficiency, and antioxidative activities. Additionally, the review examines the underlying mechanisms through which EOs exert their beneficial effects, such as antimicrobial, antioxidant, and immunomodulatory properties. In addition, the review identifies and discusses the challenges and limitations associated with the use of EOs in layer production, including issues related to dosage, administration methods, interactions with other feed components, and potential variations in EO composition and quality. By highlighting these challenges, the review offers insights into future research directions and practical recommendations for optimizing the use of EOs in layer production systems. Furthermore, this review paper distinguishes itself from existing literature by providing a comprehensive and critical review of the application of EOs in laying hen production, an area that has received limited attention previously. By synthesizing the current knowledge, this review aims to guide future investigations and facilitate the development of effective and sustainable strategies for incorporating EOs into layer production practices.